Leishmania infantum DNA detected in phlebotomine species from Puerto Iguazú City, Misiones province, Argentina - Moya, Sofía Lorián (2017)
In Puerto Iguazú City, Argentina, human and canine Visceral Leishmaniasis cases have been recorded since theyear 2010, with Leishmania infantum as the etiological agent and Lutzomyia longipalpis as its main vector. In thepresent study, polymerase chain reaction and sequencing were used to detect L. infantum DNA in 3.9% of thefemale sandflies captured in Puerto Iguazú City. This is the first report of L. infantum DNA detection inMicropygomyia quinquefer, and the second one in Lu. longipalpis and Nyssomyia whitmani for Argentina. Althoughthe detection of Leishmania DNA itself is not enough to determine a Phlebotomine species as a vector, theseresults are significant in setting the direction of further investigations of vectorial competence and capacity,necessary to define the roles of different sandflies species as specific or permissive vectors in the transmission VLcycle.